A Real-Time Electricity Price Decision Model for Demand Side Management in Wind Power Heating Mode - Li, Qiang; Li, Jian; Huang, Zhengyong; Fan, Fulin; Teng, Weijun (Frontiers in Energy Research, 2021)
The problem of wind power curtailment (WPC) during winter heating periods in China’s “Three North regions” is becoming worse. Wind power heating, though being an effective way to increase wind power consumptions, is constrained by high electric heating costs under a peak-to-valley electricity price pattern. This paper develops a real-time price (RTP) decision model which adjusts the time-varying RTPs within an acceptable range of heating users based on the WPC distribution over a particular dispatch day. The lower RTPs accompanying the higher WPC can guide the electric heating user side equipped with regenerative electric boilers (REBs) to actively increase REB imports to absorb additional wind generation. Then the demand side response using REBs under the RTP scheme is optimised to minimise the total heating cost met by electric heating users while assisting in the large-scale wind generation accommodation. The total heating costs and WPC reductions under different heating scenarios are compared and discussed alongside the effectiveness of the RTP-based demand side management in terms of reducing the WPC and heating costs and increasing the feasibility of wind power heating during winter heating periods.